Analisis Peran Petani Kopi Sukamakmur Dalam Mewujudkan Kontinuitas Pasokan Kopi Yang Berkualitas Untuk Home Coffee Roastery Bogor - Andarini, Safina Sekar; Hadi, Cecilia Sri (Prodi Pariwisata dan LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Indonesia has many rich natural resources, especially plantations and agriculture. This country has great potential and is considered the second largest producer in the world after Brazil. In addition, coffee agrotourism and coffee plantations promote sustainable aspects of tourism. Farmers are the main actors who play a role in increasing crop productivity. With demand for coffee increasing every year, how do farmers maintain continuity of coffee supply? This then became the basis for the birth of research entitled